2017
DOI: 10.1038/srep39874
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of cesium isotope concentrations and atom ratios in zooplankton in the Pacific off the east coast of Japan

Abstract: After the Fukushima Daiichi Nuclear Power Plant accident in March 2011, concentrations of cesium isotopes (133Cs, 134Cs, and 137Cs) were measured in zooplankton collected in the Pacific off the east coast of Japan from May 2012 to February 2015. The time series of the data exhibited sporadic 137Cs concentration peaks in zooplankton. In addition, the atom ratio of 137Cs/133Cs in zooplankton was consistently high compared to that in ambient seawater throughout the sampling period. These phenomena cannot be expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…So-called Cs balls, which are particles with a diameter of a few micrometers containing extremely high 137 Cs concentrations (0.66-3.27 Bq/particle), were released into the air by the accident (Adachi et al 2013). Recently, Ikenoue et al (2017) have hypothesized that consistently high but variable concentrations of 137 Cs in zooplankton collected from the waters off Fukushima and nearby prefectures, compared with concentrations in the ambient seawater, are mainly attributable to the presence of 137 Cs-enriched particles. Although Cs balls or 137 Cs-enriched particles have not yet been reported in marine sediments, it is possible that the concentration variability in sediments might be at least partially due to the presence of such particles.…”
Section: Distributions Of 137 Cs Concentrations In Surface Sedimentmentioning
confidence: 99%
“…So-called Cs balls, which are particles with a diameter of a few micrometers containing extremely high 137 Cs concentrations (0.66-3.27 Bq/particle), were released into the air by the accident (Adachi et al 2013). Recently, Ikenoue et al (2017) have hypothesized that consistently high but variable concentrations of 137 Cs in zooplankton collected from the waters off Fukushima and nearby prefectures, compared with concentrations in the ambient seawater, are mainly attributable to the presence of 137 Cs-enriched particles. Although Cs balls or 137 Cs-enriched particles have not yet been reported in marine sediments, it is possible that the concentration variability in sediments might be at least partially due to the presence of such particles.…”
Section: Distributions Of 137 Cs Concentrations In Surface Sedimentmentioning
confidence: 99%
“…Radiocesium-bearing microparticles (CsMPs) have been found since the FDNPP accident in a variety of samples, including aerosols, soil, river water, forest leaves, vegetables, and oceanic zooplankton [ 7 16 ]. In addition to mineralogical and chemical analyses, techniques employed in these studies have included use of an imaging plate, which is well suited for identification of heterogeneously located radioactive particles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mineralogical and chemical analyses, techniques employed in these studies have included use of an imaging plate, which is well suited for identification of heterogeneously located radioactive particles. Ikenoue et al [ 7 ] have suggested that the presence of highly radioactive particles probably explains the consistently higher 137 Cs/ 133 Cs ratios in oceanic zooplankton than in seawater. It is thus possible that the variability of radiocesium concentrations in seafloor sediments is due to the presence of heterogeneously distributed radioactive particles.…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals further result in oxidation, DNA damage, and inflammation in the body [1,3,4]. Currently, the probability of radiation exposure in human beings is increased due to the wide use of nuclear energy in modern society, which makes the development of effective radioprotective agents an urgent task [5][6][7].Celastrol, also known as tripterine, is a pentacyclic triterpenoid that belongs to the family of quinone methides [8][9][10][11][12][13][14][15]. It is a natural compound extracted from the root of Chinese medicinal plants Tripterygium wilfordii (Thunder god vine) and Celastrus regelii.…”
mentioning
confidence: 99%
“…Free radicals further result in oxidation, DNA damage, and inflammation in the body [1,3,4]. Currently, the probability of radiation exposure in human beings is increased due to the wide use of nuclear energy in modern society, which makes the development of effective radioprotective agents an urgent task [5][6][7].…”
mentioning
confidence: 99%